Evaluation of Diagnostic Potential of Epigenetically Deregulated MiRNAs in Epithelial Ovarian Cancer - Kumar, Vivek; Gupta, Sameer; Chaurasia, Amrita; Sachan, Manisha (Frontiers in Oncology, 2021)
Background: Epithelial ovarian cancer (EOC) is one of the most lethal gynecological malignancy among women worldwide. Early diagnosis of EOC could help in ovarian cancer management. MicroRNAs, a class of small noncoding RNAs molecules, known to be involved in post-transcriptional regulation of ~ 60% human genes. Aberrantly expressed miRNA associated with disease progression are confined in lipid or lipoprotein and secreted as extracellular miRNA in body fluid such as plasma, serum and urine. miRNAs are stably present in circulation and recently have gained an importance to serve as minimally invasive biomarker for early detection of epithelial ovarian cancer. Methods: Genome-wide methylation pattern of six EOC and two normal ovarian tissues samples revealed differential methylation regions of miRNA gene promoter through MeDIP-NGS sequencing. Based on log2FC and p-value, three hypomethylated miRNAs (miRNA-205, miRNA-200c, and miRNA-141) known to have potential role in ovarian cancer progression were selected for expression analysis through qRT-PCR. Expression of selected miRNAs was analysed in 115 tissue (85 EOC, 30 Normal) and 65 matched serum (51 EOC and 14. Normal) samples. Results: All three miRNAs (miRNA-205, miRNA-200c, and miRNA-141) showed significantly higher expression in both tissue and serum cohorts when compared with normal controls (p<0.0001). The receiver operating characteristic curve analysis of miRNA-205, miRNA-200c and miRNA-141 has area under curve (AUC) of 87.6 (p<0.0001), 78.2 (p<0.0001), and 86.0 (p<0.0001) respectively in advance-stage serum samples however ROC has AUC of 88.1 (p<0.0001), 78.9 (p<0.0001), and 86.7 (p<0.0001) respectively in early-stage serum samples. Combined diagnostic potential of three miRNA in advance-stage serum samples and early-stage serum samples has AUC of 95.9 (95% CI: 0.925-1.012; sensitivity=96.6% and specificity=80.0%) and 98.1 (95% CI: 0.941-1.021; sensitivity=90.5% and specificity=100%), respectively. Conclusion: Our data correlates the epigenetic deregulation of the miRNA genes with their expression. In addition miRNA panel (miRNA-205 + miRNA-200c + miRNA-141) has much higher AUC, sensitivity, and specificity to predict EOC at an early stage both in tissue and serum samples.